AB0596 PREDICTORS, LONG TERM CLINICAL AND TREATMENT OUTCOMES IN SOUTH ASIAN PATIENTS WITH IDIOPATHIC INFLAMMATORY MYOSITIS: A SINGLE CENTER STUDY. (2nd June 2020) - Nair, A.; Goel, R.; Chebbi, P.; Mathew, A.; Ganapati, A.; Rebekah, G.; Yadav, B.; Prakash, J. A. J.; Danda, D.; Mathew, J.
Abstract : Background: Idiopathic inflammatory myositis (IIM) are a heterogeneous group of immune-mediated disorders with varied presentations and multiple organ involvement. Data on long term outcome among South Asian patients with IIM is sparse. Objectives: To study the long term clinical outcome, treatment responses and factors predicting outcome among adult patients with IIM Methods: Patients diagnosed as 'Idiopathic Inflammatory Myositis' under the department of Clinical Immunology and Rheumatology at CMC, Vellore, India were screened retrospectively. Patients aged 18 years and above, satisfying Bohan and Peter criteria, having follow up of one year or more with atleast two outpatient or inpatient visits between January 2010 and April 2019 were included in this study. Those patients with connective tissue disease associated myositis were not included. Details on muscle weakness, extramuscular involvement, muscle enzymes and treatment administered were recorded at baseline, 3, 6, 12, 18, 24 months and yearly thereafter. After assessing their cumulative response, categorization of patients into complete and partial responders was done. Complete responders were defined as patients with persistent muscle power of more than 4/5 and/or MMT 8 more than 76/80, complete resolution of skin, articular and lung involvement (if any) as well as muscle enzymes less than twice the upper limit of normal without any documented flares during the entire follow up period. Patients not satisfying the said criterias were grouped as Partial responders. Disease free survival duration was also analyzed. Results: Out of 310 patients of IIM identified, 187 (60.3%) patients satisfied the inclusion criteria. Women were 2.2 times more than men and mean age at symptom onset was 35.7±12.6 years. Dermatomyositis was the predominant myositis subtype seen. All patients were put on steroids with the mean dose being 45.9 ± 18.6 mg/day. At baseline, the key immunosuppressants used were methotrexate in 44.9% and mycophenolate in 37.6% patients. The median follow up duration was 48 (25-80) months. An associated malignancy was diagnosed in 3.2% after a median duration of 24.5 months. Five patients expired after a median duration of 80 months from diagnosis. Normal muscle power was attained in 76.1% patients and 88.6% were vocational by the last follow up visit. Steroids were discontinued in 56.7% patients after a median duration of 24 months (p=0.0002). Discontinuation of the immunosuppressant was feasible in 10.2% patients after a median duration of 44 months. Assessment of the cumulative responses revealed a relapsing and remitting course in 45.9%. Outcome predictors in univariate analysis were Jo-1 status, presence of arthritis, interstitial lung disease and pericardial effusion at baseline. On multivariate analysis, absence of pericardial effusion (p=0.011) and interstitial lung disease (p=0.067) at baseline were found to be predictors of complete response. Disease free survival probability estimated at 5 years and 10 years was 91.6% and 72.4% respectively. Estimating the probability gender wise, males achieved disease free status earlier than females. Conclusion: A favorable clinical and functional outcome was seen in a significant proportion of these patients with IIM on long term follow up. Pericardial effusion and ILD were identified as predictors of poor clinical outcome. References: [1]Taborda AL, Azevedo P, Isenberg DA. Retrospective analysis of the outcome of patients with idiopathic inflammatory myopathy: a long-term follow-up study. Clin Exp Rheumatol. 2014 Apr; 32(2):188–93. Acknowledgments: Nil Disclosure of Interests: None declared